Carbohydrate mouth rinse improves cycling time-trial performance without altering plasma insulin concentration - Murray, K. O.; Paris, H. L.; Fly, A. D.; Chapman, R. F.; Mickleborough, T. D. (Journal of Sports Science & Medicine, 2018)
Rinsing the mouth with a carbohydrate solution has been shown to improve exercise performance in a manner similar to carbohydrate ingestion. However, the underlying mechanisms behind these ergogenic benefits remain unclear. This study evaluated whether rinsing the mouth with a carbohydrate solution alters plasma insulin and glucose concentration during the initial stages of a 40 km cycling time-trial. Eight trained, competitive cyclists [age (mean ± SEM) = 24 ± 2 y; VO2max = 64.5 ± 2.2 ml·kg-1·min-1] completed three simulated 40 km time-trials comprised of a familiarization trial, a carbohydrate condition (CHO) and a placebo mouth rinse condition (PLA). In the two mouth rinse conditions, rinsing was administered prior to onset of exercise and every 5 km throughout exercise. Plasma insulin was collected at 5 km intervals throughout the first 25 km, and glucose samples were collected at 5 km intervals throughout the exercise bout. No change in plasma insulin was detected between conditions (p = 0.638, ES < 0.03) for the first 25 km of the time-trial. Likewise, plasma glucose concentration did not differ between CHO and PLA (p = 0.801, ES < 0.01) and remained relatively stable throughout exercise. Time to complete the 40 km time-trial was significantly faster for CHO (67.1 ± 1.1 min) compared to PLA [67.9 ± 1.0 min; (P = 0.028, ES 0.27)]. Performance time was faster by an average of 1.1% (95% confidence interval range 0.2-2.0%) in the CHO condition. Exercise intensity (% VO2max) throughout the trial was similar between conditions (p = 0.846). Respiratory exchange ratio was not significantly different between conditions (0.88 ± 0.01 for PLA, and 0.91 ± 0.01 for GLC; p = 0.081). Performance gains elicited by a carbohydrate mouth rinse occurred independently of changes in plasma insulin concentration.